2021
DOI: 10.3389/fpsyt.2021.727496
|View full text |Cite
|
Sign up to set email alerts
|

Co-design of Guidance for Patient and Public Involvement in Psychedelic Research

Abstract: Within the context of scientific research, patient and public involvement (PPI) is defined as research performed “with” or “by” patients and members of the public, rather than “to,” “about”, or “for” them. When carried out systematically and thoughtfully, PPI has the potential to strengthen the quality and impact of research by fostering accountability, transparency, and relevance. There exist numerous guidelines, frameworks and tools for supporting PPI, however, these do not account for the unique challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…1.1.1 Depression: All contributors reported feelings of depression as part of their everyday life. While some contributors reported feelings of depression preceding their pain (5), all reported that their mental wellbeing and subsequent depression were impacted by the chronification of their pain. Several contributors (3) reported feeling suicidal due to their pain.…”
Section: Thematic Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…1.1.1 Depression: All contributors reported feelings of depression as part of their everyday life. While some contributors reported feelings of depression preceding their pain (5), all reported that their mental wellbeing and subsequent depression were impacted by the chronification of their pain. Several contributors (3) reported feeling suicidal due to their pain.…”
Section: Thematic Analysismentioning
confidence: 99%
“…1.2.2 Acceptance of Pain: Seven contributors reported increased acceptance of their situation and found this to be helpful in their general experience of pain. 1.2.5 Increased Compassion: Eight contributors felt more compassion toward themselves (6) and others (5).…”
Section: Thematic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…While this trial is one of many exploring psychedelics in mental health treatment, we wish to emphasise how incorporating the voices of those with lived experience has not been beneficial for adapting the psychedelic-therapy approach to this population, but has also been a rewarding experience for researchers and focus group attendees alike. We encourage the integration of PPI initiatives into future psychedelic research, and guidance for doing so has been presented by Close et al (59).…”
Section: Discussionmentioning
confidence: 95%